Chemical and physical reinforcement of hydrophilic gelatin film with di-aldehyde nanocellulose - Kwak, Hyo Won; Lee, Hohyun; Park, Subong; Lee, Min Eui; Jin, Hyoung-Joon (ELSEVIER, 2020)
Gelatin is a representative hydrophilic protein material with remarkable biocompatibility and biodegradability. From the aspect of materials processing, gelatin also has the advantage that its entire fabrication process can be performed in an aqueous solution. However, practical application of various gelatin materials-in particular gelatin films-has thus far been limited because of their weak mechanical properties and vulnerability under aqueous environments. To overcome these disadvantages, both physical reinforcement approaches and chemical cross-linking agents have been tested. However, little research has been done to make these two roles work at the same time. In this study, cellulose nanocrystals containing aldehyde groups were prepared via a periodate oxidation process and used for cross-linkable reinforcement of gelatin-based bio-composite films. The results revealed that the di-aldehyde cellulose nanocrystal (D-CNC) could react and covalently cross-link with the amine group of the gelatin molecules via Schiff base formation and compared with neat CNC. The gelatin bio-composite film reinforced with the prepared D-CNC exhibited excellent tensile properties and water resistance, and its mechanical and hydrophilic properties could be easily controlled by adjusting the D-CNC content and was greater than addition of same amount in CNC. Therefore, D-CNC will facilitate the widespread use of existing water-soluble polymers, especially natural hydrophilic proteins and can be used in conventional application fields such as the food, pharmaceutical, and biomedical industries. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: BACTERIAL CELLULOSE NANOCRYSTALS; FISH GELATIN; NANOCOMPOSITE FILMS; DIALDEHYDE CELLULOSE; POLY(VINYL ALCOHOL); COMPOSITE FILMS; ANTIMICROBIAL PROPERTIES; PERIODATE-OXIDATION; SODIUM ALGINATE; CROSS-LINKING